Urgensi Personal Selling Sebagai Teknik Pemasaran Pada Bank Rakyat Indonesia Kantor Cabang Pasuruan - Wisnu Erlangga; Himatul Hasanah (Penerbit dan Percetakan CV. Picmotiv, 2026)
This study aims to analyze the urgency, opportunities, and challenges of personal selling as a marketing strategy at Bank Rakyat Indonesia (BRI) Pasuruan Branch Office, and examine its integration with Islamic Economic values. Amidst the development of digital banking, personal selling remains a crucial approach because it fosters two-way communication, improves customer understanding, and strengthens trust through face-to-face interactions, especially in non-digital segments such as MSMEs and traditional communities. This study uses a descriptive qualitative approach, collecting data through interviews, observations, and documentation, and its validity is tested using source triangulation. The results show that personal selling plays a strategic role in education, service differentiation, and building long-term relationships with customers. In addition, this strategy opens opportunities to increase loyalty and product cross-selling, but it also faces challenges such as limited reach, high operational costs, and the need to adapt to digital technology. Furthermore, the implementation of personal selling at BRI KC Pasuruan has integrated the values ​​of nubuwwah from an Islamic Economic perspective, namely shiddiq, amanah, tabligh, and fathanah. These values ​​not only serve as a foundation for ethics but also serve as a strategy for increasing customer trust and loyalty. Therefore, personal selling focuses not only on achieving sales targets but also on creating sustainable relationships based on Islamic values.